PENERAPAN METODE HAVERSINE PADA SISTEM INFORMASI GEOGRAFIS UNTUK PENENTUAN KELAYAKAN ZONASI SEKOLAH BERBASIS ANDROID - Artika Rahayu; Arief Tri Arsanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The implementation of the zoning policy in Indonesia's New Student Admission (PPDB) aims to ensure equitable access to education. However, discrepancies between public distance calculations and the official straight-line (great-circle) distance standard often lead to misunderstandings. This study aims to design and implement an Android-based Geographic Information System (GIS) for determining school zoning eligibility using the Haversine method. The research employed an applied research approach with the Waterfall software development model, consisting of requirements analysis, system design, implementation, testing, and maintenance. The application was developed using Flutter, Google Maps API, and Firebase Firestore as the database platform. System functionality was evaluated through Black Box Testing, while the accuracy of the Haversine calculation was validated by comparison with manual calculations. The results indicate that the application successfully determines zoning eligibility based on a maximum distance of 5 km, displays user and school locations in real time, and achieves high computational accuracy with an error rate of only 0.16% compared to manual calculations. The integration of the Haversine method with geospatial technologies enhances the transparency and objectivity of school zoning assessment. Therefore, the developed system provides an effective alternative for prospective students to access fast, accurate, and reliable zoning eligibility information through Android devices.